Effect of chemical pretreatment on pulp and paper characteristics of bamboo gigantochloa scorthechinii kraft fibers - Mohamed @ Asa'ari, Ainun Zuriyati; Muhammad, K. I.; Halis, Rasmina; H. A., Hazwani; A., Sharmiza; Abu Kassim, Naziratulasikin; Latifah, J. (IOP Publishing, 2018)
In chemical pulping process, lignin is targeted to be dissolved and eliminated as much as possible in order to obtain better fiber separation. A primary study was carried out to investigate the effect of sodium hydroxide pretreatment prior to bamboo chemical pulping. The selected bamboo species was Gigantochloa scortechinii which is a well-known bamboo in Malaysia. The bamboo chips were soaked in 2 % sodium hydroxide solution for 6 hours at 60 °C. These treated chips were cooked at 14 % and 18 % of alkali active via kraft pulping process. The unbleached pulp was obtained and made into paper. The pulp and paper were tested according to pulp yield, pulp freeness, paper optical, paper physical and paper mechanical properties. The results exhibited that by using treated bamboo chips, the value of pulp yield, freeness and paper brightness increasing. Slight decrement was observed for mechanical paper properties such as tensile, tear and burst strength. Chemical pretreatment prior to pulping process was investigated to offer significant effects to the pulp and paper properties of bamboo Gigantochloa scortechinii. Hence, mild kraft pulping can be carried out to produce bamboo unbleached pulps. In addition, dependency on bleaching sequences can also be declined.